Cellular Origin(s) of Congenital Diaphragmatic Hernia - Edel, Gabriëla G.; Schaaf, Gerben; Wijnen, Rene M. H.; Tibboel, Dick; Kardon, Gabrielle; Rottier, Robbert J. (Frontiers in Pediatrics, 2021)
Congenital diaphragmatic hernia (CDH) is a structural birth defect characterized by a diaphragmatic defect, lung hypoplasia and structural vascular defects. In spite of recent developments, the pathogenesis of CDH is still poorly understood. CDH is a complex congenital disorder with multifactorial etiology consisting of genetic, cellular and mechanical factors. This review explores the cellular origin of CDH pathogenesis in the diaphragm and lungs and describes recent developments in basic and translational CDH research.